2. Development of Artistic Creativity in Students by Studying and Applying Ornamental Motives in the Textile Art Course - Arbuz-Spatari Olimpiada (Sciendo, 2020)
In the training process within the textile art course, a system of methods of studying and applying the elements of the plastic language is used within the proposed methodology, which was followed by the development of artistic creativity in the students of the plastic art faculty. These methods were developed and applied in the course of textile art for the compartments: elaboration of creative compositions; consciously applying the elements of plastic language; studying and applying ornamental motifs in the textile art course. The methods developed for the textile art course, in their interaction, will contribute to the development of the student's artistic creativity, helping him to execute the creative product in the field of textile arts.